Molecular Docking and Dynamics Simulation for Searching Anti-Cancer Compounds of Piperlongumine Derivatives that Have Potential as an Inhibitor Against MAO-B (Monoamine Oxidase B) - Agus Salim; Raden Rara Fadhila Kirana Nugrahani; Yolanda Amalia; Suwardi Suwardi (Indonesian Journal of Chemistry and Environment, 2023)
The docking of the piperlongumine molecule and its derivatives has been carried out to find molecules that have the potential as anti-cancer. A total of 18 ligands were docked to the 2v5z protein using the autodock4 and autodock vina programs. The binding energies of piperlongumine and piperlongumine derivatives [R1 = CH3 and R2 = H] were -8.6 kcal/mol and -9.3 kcal/mol, respectively. Based on molecular dynamics simulations, the hydrogen bond interaction fraction was dominated by GLN 206 residue in both the SAG (88%)  and piperlongumine derivatives ((R1=CH3, R2 = H)(93%) ligand, for this reason, this piperlongumine derivative molecule is predicted to have potential as MAO B inhibitor.